DRAMATIC LANGUAGE STYLES FOUND IN COSMETIC PRODUCT ADVERTISEMENTS ON TELEVISION - Heni Alghaniy Maulidina; Ivan Achmad Nurcholis (Penerbit Lafadz Jaya, 2022)
Language style refers to how people use words and tone of voice to manipulate others and control their interactions to convey messages or ideas. Language style is defined by the selection and selection of linguistic forms produced by a person or group of people. The purpose of this study is to identify and classify the dramatic language styles found in cosmetic advertisements. In this qualitative research, the author uses a descriptive method through several stages: research design, data sources, research instrument, techniques of collecting data, and techniques of analysis data. The focus of this research is the analysis of dramatic language style in television cosmetic advertisements. In this analysis, it can be concluded that dramatic language style is a style of language that exaggerates and sometimes does not match reality.